PENGARUH KARAKTERISTIK PEKERJAAN DAN MOTIVASI TERHADAP KOMITMEN ORGANISASIONAL SERTA DAMPAKNYA TERHADAP KINERJA GURU - Mulyani, Sri (Faculty of Economics and Business Universitas Jenderal Soedirman, 2014)
This research of aim to test and analyze the influence of job characteristic andmotivation to organizational commitment teachers in Country Junior High School 21and Country Junior High School 26 Semarang and also to test and analyze the influenceof job characteristic, organizational commitment and motivation to performance teachers in Country Junior High School 21 and 26 Semarang.Population in this research are teachers in Country Junior High School 21 and26 Semarang counted 150 people. The technique sampling in this research use samplingpurposive with sample criterion, that is teacher in Country Junior High School 21 and26 Semarang which have PNS and work to minimize 5 year hence obtained by samplecounted 118 people. This research represent quantitative research which analyze andprove research hypothesis. Data analysis use multiple linear regression analysis.Pursuant to data analysis can be taken by the following conclusion of job characteristic have an effect on positive to organizational commitment, progressively precisely done by job characteristic is teacher with membership had, hence excelsior alsocommitment to organization. Motivation has an effect on positive to organizationalcommitment, motivation excelsior learn in job, hence excelsior also commitment learnto organization. Work characteristic have an effect on positive to teacher performance,progressively precisely done by job characteristic is teacher with membership had,hence excelsior will also its performance. Motivation have an effect on to performance,teacher motivation excelsior, hence excelsior also its performance. OrganizationalCommitment have an effect on to teacher performance, commitment excelsior learn atorganization, hence excelsior also its performance. Organizational job characteristicmediation Commitment to performance learn. This matter indicate that job characteristic with in mediation by organizational commitment will be able to create high performance at teacher Country Junior High School 21 and 26 Semarang. Commitment Organizational do not mediation motivate to performance learn. This matter indicate thatmotivation without in mediation by organizational commitment, motivation learn Country Junior High School 21 and 26 Semarang have earned to yield high teacher performance.